Improving breeding in sub-Saharan Africa. Project profile. - International Potato Center (International Potato Center, 2019)
Sweetpotato, particularly the orange-fleshed varieties, has under-exploited potential to boost food security, raise household incomes, improve nutrition and help build resilience to climate change among poor farming families across sub-Saharan Africa. This project aims to develop the critical genetic, data and human resources required to enhance sweetpotato breeding systems and accelerate the release of new varieties to farmers.